Adsorption equilibrium studies of a simulated textile effluent containing a wool reactive dye on gallinaceous feathers - Freitas, Olga M. (2016)
Gallinaceous feathers (from Gallus gallus domesticus, strains Cobb 500 and Label) were used as adsorbent for colour removal from a simulated textile effluent containing a wool reactive dye, the Yellow Lanasol 4G (CI Reactive Yellow 39). A brief chemical and physical characterisation of feathers was performed. Equilibrium studies at different selected temperatures, in the range 10–60 °C, were carried out. The equilibrium data were analysed using the Freundlich and Langmuir isotherm models. Adsorption capacity strongly increases with temperature. A maximum adsorption capacity of around 300 mg g-1 was obtained for Gallus gallus feathers, strain Cobb 500, at 60 °C, while for strain Label, 200 mg g-1 was obtained at 50 °C. For each type of feather a generalised model, valid for a given temperature range, was obtained. The isosteric heat of adsorption calculated was positive, so the mechanism involved in the adsorption process should correspond to endothermic chemisorption. This study provides important information concerning the use of gallinaceous feathers without any chemical treatment for colour removal from real textile wastewaters. The results in this study indicated that gallinaceous feathers, when compared with activated carbon, open promising perspectives concerning their utilisation for colour removal from textile effluent discharged at high temperatures; moreover, it would be an alternative for the valorisation of this waste.